Applying Fermented Rice Washing Water and Organic NPK to Increase Plant Growth and Production Caisim Mustard Greens (Brassica juncea L) - Nursamsul Kustiawan; Siti Zahrah; Maizar (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
The demand for vegetables, particularly mustard greens, in Riau Province continues to rise alongside the overall increase in vegetable consumption. However, current production levels are insufficient to meet this demand, necessitating imports from neighboring regions such as West Sumatra and North Sumatra. Therefore, there is a pressing need to enhance local production. This study aimed to evaluate the effects of varying concentrations of fermented rice washing water and organic NPK on the growth and yield of mustard greens (Brassica juncea L.). The research employed a Factorial Completely Randomized Design, which included two factors. The first factor was the concentration of fermented rice washing water, with four treatment levels: 25%, 50%, 75%, and 100%. The second factor was the application of organic NPK, also with four treatment levels: no organic NPK, 2.25 g/plant, 4.5 g/plant, and 6.75 g/plant. The parameters observed included the number of leaves, wet weight, economic weight, dry weight, net assimilation rate, and relative growth rate. The results indicated that the combination of fermented rice washing water and organic NPK had a significant effect on all observed parameters except for dry weight, with the optimal treatment being a concentration of 100% and 6.75 g of organic NPK per plant. The application of rice washing water significantly influenced all observed parameters, with the best treatment being fermented rice washing water at a concentration of 100%. Additionally, the effect of organic NPK was significant across all observed parameters, with the optimal treatment being 6.75 g per plant. The combination of fermented rice washing water and organic NPK effectively enhanced the growth and production of mustard greens, resulting in a production yield of 20.2 tons per hectare.